Socio-Economic Dynamics and Management Practices Tailed for Palla Sheep of Andhra Pradesh: Insights into a Traditional Livelihood - Bhavani, Killana Eswar; Vani, Sunkara; Sakunthala Devi, Kopparthi; Suresh Babu, Dasineni; Reddy, Punuru Pandu Ranga; Siraj, Shaik Mohammad (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study was carried out to explore the socio-economic status and husbandry practices followed by 88 shepherds rearing Palla  sheep from 304 flocks of 38 mandals of four revenue divisions of Nellore district which is the sole breeding tract of Palla sheep in India.  Most of the sheep flocks (95%) were reared by family members and majority of shepherds (79.93%) raised sheep using both stationary  and migratory methods. The average migration distance of Palla flocks was 74.88 km. Majority of the farmers (92.04%) provided shelter  at night and the nature of houses varied from part of residence (61.35%) to separate houses (38.65 %). The open and closed type of  housing was followed in 59% and 40% of the flocks, respectively, and most of the sheep habitations were having thatched roofs (68.18%).  Grazing (79.50%) in the field was the popular method of feeding and varied from 6 h to more than 8 h. Majority were having primary  education (73.86%) and the family size was medium (59%) with an average of 5.22 persons per family. Most of the shepherds choose  ovine husbandry as a primary occupation (93.18%) and 67% were earning between Rs. 75,000 to 1,00,000 per annum. The mortality  rate in lambs and adults was more than 20% and 6-10%, respectively.
Keywords: Breeding tract; Husbandry practices; Palla sheep; Socio-economic status